Pengawasan Pemerintah Terhadap Pengawasan Hutan Sebagai Upaya Pencegahan Kerusakan Hutan Untuk Lahan Pertanian: (Studi Desa Selante Kecamatan Plampang Kabupaten Sumbawa) - Adri Ahmadi; Arief Rahman (Private Law, 2023)
This study aims to analyze the impact of forest destruction as a result of changes in the function of the forest in the corn farming area, why the government is not effective in protecting forests, and how the government has made efforts to overcome forest damage. This study uses empirical research. The approach used is the statutory, conceptual and sociological approach. Sources of data used are field data and literature. Techniques/How to obtain data is done by interview technique. The analysis used in this research is qualitative. Based on the research results, the impact of forest damage in the Sumbawa Regency is unpredictable weather conditions from year to year, flooding, erosion, and sedimentation of the forest floor surface, which is starting to erode. Supervision is ineffective due to a lack of Human Resources (HR). Efforts made by Sumbawa Regency in overcoming forest damage are forest and land rehabilitation with a self-management scheme of local community groups.